Bulk and single-cell RNA-sequencing analyses revealed potential key genes and the role of CCL19/CCL21-CCR7 axis in hidradenitis suppurativa - Xiaodong Lai; Yan Yang; Haini Zhang; Chong Zhang; Meng Wang; Wanxin Chen; Baoxi Wang; Yan Yan (PLoS ONE, 2025)
Hidradenitis suppurativa (HS) is a chronic inflammatory skin disorder, affecting the pilosebaceous unit in apocrine gland-rich areas, characterized by painful nodules, abscesses and draining tunnels. The underlying molecular and immunological mechanisms remain poorly understood. This study aimed to identify key gene expression patterns, hub genes, and analyze the potential role of the CCL19/CCL21-CCR7 axis in HS lesions and peripheral blood using bulk and single-cell RNA sequencing analyses. By employing an integrative approach that included three machine learning methods and subsequent validation on an independent dataset, we successfully identified AKR1B10, IGFL2, WNK2, SLAMF7, and CCR7 as potential hub genes and therapeutic targets for HS treatment. Furthermore, our study found that CCL19 and CCL21 may originate from various cells such as fibroblasts and dendritic cells, playing a crucial role in recruiting CCR7-associated immune cells, particularly Treg cells. The involvement of the CCL19/CCL21-CCR7 axis in HS pathogenesis suggests that other CCR7-expressing cells may also be recruited, contributing to disease progression. These findings significantly advance our understanding of HS pathogenesis offer promising avenues for future CCR7-targeted therapeutic interventions.